The Role of Bhabinkamtibmas through Counseling Guidance in Preventing Sexual Crimes against Children in the Kuningan Police Jurisdiction - Ivan Pradipta (Advances in Police Science Research Journal, 2021)
The focus of this thesis research is motivated by an increase in sexual crimes against children in the Kuningan Police jurisdiction that impacts victims both physically and psychologically. Therefore, a study was conducted aimed at describing the general picture of sexual crimes against children in the Kuningan police jurisdiction, describing the role of the Kuningan Police Bhabinkamtibmas through Counseling Guidance in preventing sexual crimes against children, and identifying the factors that influence the role of Bhabinkamtibmas through Counseling Guidance in prevent sexual crimes against children. Theories and concepts used in answering problems are Routine Activity Theory, Crime Prevention Theory, Management Elements Theory, Role Concepts, Bhabinkamtibmas Concepts, Guidance Counseling Concepts, Sexual Crime Concepts against Children, and the Concept of Community Policing Success. The study was conducted with a qualitative approach and analytical descriptive research type. The findings of this study are that sexual crimes against children in the Kuningan police jurisdiction have a majority of perpetrators aged 15-24 years, victims aged 13-15 years, as well as families of victims who work outside the city so they are less able to supervise victims. Counseling by Bhabinkamtibmas is still not maximized which has an impact on the increasing number of sexual crimes against children. There are internal and external factors that have not been optimally fulfilled in the implementation of counseling by Bhabinkamtibmas. Such as the lack of competence and the limited number of Bhabinkamtibmas personnel, the material does not discuss sexual crimes against children, facilities and infrastructure that have not been evenly fulfilled, and the lack of coordination with relevant agencies. , the selection of more selective personnel, the provision of more intensive rewards and punishments, the fulfillment of Sarpras, and the increased use of the Binmas Apparatus application. Keyword : Bhabinkamtibmas, Guidance for Counseling, Sexual Crimes against Children